Assessment of Dysfunctional Cognitions in Binge-Eating Disorder: Factor Structure and Validity of the Mizes Anorectic Cognitions Questionnaire-Revised (MAC-R) - Carrard, Isabelle; Rothen, Stephane; Kruseman, Maaike; Khazaal, Yasser (Frontiers in Psychology, 2017)
Background: Dysfunctional cognitions regarding weight and shape and their implications for self-esteem are considered core features of anorexia nervosa and bulimia nervosa. However, they have also been associated with the severity of binge eating disorder (BED). Therefore, they should be screened with appropriate instruments to tailor treatment to individual patient needs. The Mizes Anorectic Cognitions-Revised (MAC-R) is a self-report questionnaire that lists dysfunctional cognitions related to three hypothesized core beliefs typical of the psychopathology of eating disorders: weight and eating as the basis of approval from others; the belief that rigid self-control is fundamental to self-worth; and the rigidity of weight- and eating-regulation efforts. Objectives: The goal of the study was to confirm the factor structure and to assess the validity of the MAC-R among a sample that met full-threshold and subthreshold criteria for BED. Methods: We used data of women meeting full-threshold (n=94) and subthreshold (n=22) criteria for BED to conduct confirmatory factor analyses and to compute Spearman’s correlations, in order to assess factorial, convergent and discriminant validity. Results: Two models having a structure of three factors with or without a total score proved to be acceptable. The MAC-R total score was correlated with questionnaires assessing dimensions related to eating disorder psychopathology, adding to the validity of the questionnaire. Conclusion: These results were similar to those found in studies on the psychometric properties of the MAC among samples with anorexia nervosa or bulimia nervosa, encouraging the use of the MAC-R as a research or clinical tool in order to further document the core beliefs underlying BED. A further validation with a larger sample size might strengthen these findings.